(untitled) (Revista de Psicología, 2019)
Study the associations between personality traits the optimal experience in university teachers have a therapeutic value, then, using the appropriate assessment tools could favor a more accurate diagnosis and more effective treatment, in order to produce levels of higher satisfaction in the teaching task. Objective: To analyze the relationship between optimal experience or Flow and personality traits, in Higher Level teachers. Method: quantitative, descriptive-correlational research. Participants: intentional sample of 59 Higher Level teachers from Mendoza, of which only 46 answered both questionnaires. Instruments: the adaptation for adults of the Optimal Experience Questionnaire (Mesurado, 2008) and the Neo Inventory of the Revised Personality (NEO-PI-R), Argentine adaptation of Richaud de Minzi, Lemos and Oros (2004). For the analysis, descriptive statistics were used, including the Spearman correlation coefficient and a significance level greater than .01. Results: Neuroticism is negatively correlated with the occurrence of the optimal experience in the teachers of the sample, while Extraversion, Pleasure and Responsibility correlated positively in different measures. In turn, the Openness is the only personality factor that did not correlate with the optimal experience of the teachers in the sample.